2018
DOI: 10.3390/dj6030023
|View full text |Cite
|
Sign up to set email alerts
|

Flipping the Dental Anatomy Classroom

Abstract: The development of cognitive knowledge, motor skills, and artistic sense in order to restore lost tooth structure is fundamental for dental professionals. The course of dental anatomy is taught in the initial years of dental school, and is a component of the basic core sciences program in the faculties of dentistry. The learning objectives of the dental anatomy course include identifying anatomical and morphological characteristics of human primary and permanent teeth; identifying and reproducing tooth surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 36 publications
0
58
0
1
Order By: Relevance
“…In the process of teaching tooth morphology at other colleges and universities in China, commercially produced model teeth have been used as a means of teaching exploration [28,29]. However, the commercial model teeth have several major problems: (1) The size of the model teeth does not match the size of the gypsum blocks the students use in their carving. The commercial models are too large or too small, and it is therefore difficult to use them as an equal-scale reference when carving.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of teaching tooth morphology at other colleges and universities in China, commercially produced model teeth have been used as a means of teaching exploration [28,29]. However, the commercial model teeth have several major problems: (1) The size of the model teeth does not match the size of the gypsum blocks the students use in their carving. The commercial models are too large or too small, and it is therefore difficult to use them as an equal-scale reference when carving.…”
Section: Discussionmentioning
confidence: 99%
“…The tooth morphology course is an important basic stomatology course that mainly covers the composition, classification and anatomical features of a single tooth [1]. To master tooth morphology, students need to actually carve gypsum or wax to deepen their understanding of the characteristic shape of each tooth, establish a 3D concept of teeth, and improve their carving skills for future clinical courses (such as dental prosthetics and cariology/endodontics) and clinical work [2].…”
Section: Introductionmentioning
confidence: 99%
“…A metaanalysis reported that the FC method is associated with greater academic achievement than the traditional approach to higher-level learning outcomes in medical education [22]. Some researchers have used the FC model in stomatology education, for example, in dental anatomy [23,24], a practical preclinical dental skills course [25] and a fixed prosthodontic course [20], and have achieved satisfactory results. Only one study reported finding the FC model effective when applied in the practice plan on periodontal diagnosis and treatment [26].…”
Section: Discussionmentioning
confidence: 99%
“…The above is consistent with Lona's 30 report that students perform better in active learning contexts. KallesarianFlowerday 31 explains that these aspects increase the intrinsic motivation and commitment of students to the course, their peers, and teachers. These findings are also consistent with other studies 27 showing that the combination of personal control and student interest has a significant influence on commitment and learning.…”
Section: F I G U R E 3 Distribution Of Final Grades In the 3 Groupsmentioning
confidence: 99%